Efeito da incorporação de nanopartículas de hidroxiapatita em infiltrantes resinosos na inibição da progressão de lesões iniciais de cárie em esmalte - Rodrigues, Elvia de Araújo (2014)
Introduction: Enamel infiltrants are fluid resins indicated to recover initial enamel caries lesions. However, the application of a resinous material purely does not allow remineralization of demineralized enamel. Therefore, the incorporation of hydroxyapatite (HAP) may be a promising tool for the development of novel enamel infiltrants with improved mechanical, biological and anticaries properties. Aim: The objective of this in vitro study was to evaluate the effect of the incorporation of hydroxyapatite nanoparticles (NHAP) with different sizes into experimental infiltrants on the cross-sectional microhardness of demineralized enamel as well as on the inhibition of the progression of caries around the infiltration. Methods: After NHAP incorporation, conversion degree (CD) was evaluated in a Fourier-transform infrared spectrophotometer in triplicate for each resin. Next, 50 human enamel blocks were demineralized (solution 50% saturated of HAP, pH = 4.9 during 16h) and randomly allocated to five groups, as follows: no-treated control; commercial infiltrant, experimental infiltrant with amorphous NHAP with 10 nm, crystalline NHAP with 20 or 30 nm. After treatment, half of each block was submitted to a pH-cycling model. Enamel cross-sectional microhardness analysis was performed after treatments and pH-cycling model at the treated and adjacent areas. Data were statistically analyzed using ANOVA and Tukey's test specific for each experiment. Results: The CD of infiltrants added with NHAP of 20 (66.7%) and 30 nm (61.2%) had a statistically significant increase when compared to CD of the commercial infiltrant (p <0.001 and p = 0.006 respectively). The comercial one and the infiltrant with 10-nm amorphous NHAP increased enamel hardness when compared to the untreated control (p <0.05). After pH cycling, the experimental infiltrants with crystalline NAHP of 20 and 30 nm preserved the enamel hardness both in the infiltrated region and below as well as adjacent to it, while samples treated with the comercial infiltrant and that one with 10-nm amorphous NHAP presented decreased microhardness (p<0.05). Conclusion: The addition of crystalline NHAP in infiltrants increases resistance to demineralization of the infiltrated and adjacent enamel and may be an adjunct in combating early caries lesions on enamel.